Minimum acceptable diet intake and its associated factors among children age at 6-23 months in sub-Saharan Africa: a multilevel analysis of the sub-Saharan Africa demographic and health survey - Daniel Gashaneh Belay; Asefa Adimasu Taddese; Kasahun Alemu Gelaye (BMC, 2022)
Abstract Background Only one in five children aged below 24 months in the low-income countries feed the minimum recommended diet, and significantly varied across socio-economic classes. Though sub-saharan Africa (SSA) shares the huge burden of children under nutrition, as to our search of literature there is limited evidence on the pooled magnitude and factors associated with minimum acceptable diet (MAD) intake among children aged 6 to 23 months in the region. This study aimed to assess the pooled magnitude and associated factors of MAD intake among children aged 6-23 months in SSA using recent 2010-2020 DHS data. Methods Demographic and Health Survey datasets of SSA countries were used for this study with a total of 78,542 weighted samples. The data were cleaned using MS excel and extracted and analyzed using STATA V.16 software. A multilevel binary logistic regression model was fitted. The adjusted odds ratio (AOR) with P-value < 0.05 was taken to declare statistical significance. Results The pooled magnitude of MAD intake among children aged 6-23 months in SSA was 9.89% [95%CI: 8.57, 11.21%] ranging from 3.10% in Guinea to 20.40% in Kenya. Individual level factors such as; secondary &above women educational status [AOR = 1.41; 95%CI; 1.29, 1.53], having employed women [AOR = 1.25;95%CI;1.17,1.33], having media exposure [AOR = 1.55;95%CI;1.45,1.66], richest household wealth [AOR = 1.93; 95%CI; 1.73, 2.15], plural birth [AOR = 0.68;95%CI; 0.56, 0.82] and breastfed child [AOR = 2.04; 95%CI; 1.89, 2.21], whereas, community level factor such as rural residence [AOR = 0.74; 95%CI; 0.69, 0.79] and living in upper middle income country [AOR = 1.62; [95%CI; 1.41,1.87] were significantly associated with MAD intake. Conclusion and recommendations Minimum acceptable diet intake in SSA is relatively low. Variables such as; secondary &above maternal education, having employed mother, exposure to media, richest wealth, breast feeding child, and upper middle income country have a significant positive association, whereas having plural birth and living in rural residence have a significant negative association with MAD intake. These findings highlight that policymakers and other stakeholders had better give prior attention to empowering women, enhance household wealth status and media exposure to increase the MAD intake in the region.